Citrate and celecoxib induce apoptosis and decrease necrosis in synergistic manner in canine mammary tumor cells - Vahidi, R; Safi, S; Farsinejad, A; Panahi, N (Cellular and Molecular Biology, 2015)
Celecoxib and citrate have been shown to possess antitumor activity in a variety of cancer cells. However, the antitumor activities of these agents in canine mammary tumors have not been well demonstrated. The aim of our study was to investigate the apoptotic and antiproliferative effects of citrate and celecoxib, individually and in combination, on canine mammary tumor cell line CF41-Mg. MTT assay was performed to determine cell viability, and Annexin-PI test was performed to evaluate apoptosis induction. MTT assay results revealed that compared with the control groups, treatment groups, as both single and combined treatments, showed significant inhibition of tumor growth in a dose-dependent manner. IC50 concentrations of citrate and celecoxib were defined 26 mM and 22 µM, respectively. In another set of experiment, significant increase in cell apoptosis was observed at IC50 concentrations of citrate and celecoxib after 48h incubation. In spite of that, simultaneous treatment of cells with citrate and celecoxib eventuated with meaningful toxicity augmentation and induction of apoptosis at lower concentrations. Also necrotic cells were decreased by coadministration of the two agents. In conclusion, the present study indicates significant cytotoxic and apoptotic effects of citrate and celecoxib coadministration on CF41-Mg cells, and proposes new strategies for counteracting cancer cells proliferation and overcoming chemo resistance.